2003
DOI: 10.1001/archinte.163.17.2014
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists on Rounding Teams Reduce Preventable Adverse Drug Events in Hospital General Medicine Units

Abstract: Pharmacist participation with the medical rounding team on a general medicine unit contributes to a significant reduction in preventable ADEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
283
4
19

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(333 citation statements)
references
References 8 publications
20
283
4
19
Order By: Relevance
“…10 Additionally, pharmacist involvement on medical rounds has reduced adverse drug events by 78%. 11 The frequency of prescribing errors found in this study was similar to that found in previous literature, although the variation in the definitions limits this comparison somewhat. 12 Interestingly, the frequency of errors increased as the overall number of medication orders for the facility increased (see the ratios in Figure 2).…”
Section: Discussionsupporting
confidence: 89%
“…10 Additionally, pharmacist involvement on medical rounds has reduced adverse drug events by 78%. 11 The frequency of prescribing errors found in this study was similar to that found in previous literature, although the variation in the definitions limits this comparison somewhat. 12 Interestingly, the frequency of errors increased as the overall number of medication orders for the facility increased (see the ratios in Figure 2).…”
Section: Discussionsupporting
confidence: 89%
“…Outra estratégia recomendada é a participação do farmacêutico clínico na unidade de internação como um elemento-chave dentro da equipe de saúde para realizar o seguimento da farmacoterapia e contribuir para o uso racional de medicamentos (Kucukarslan et al, 2003;Scheneider, 2007).…”
Section: Resultsunclassified
“…[3][4][5][6][7] The presence of a pharmacist during patient care rounds and when prescriptions are written has been associated with a reduction in medication discrepancies at the ordering stage. [8][9][10] In a sample of 98 emergency department visits, the accuracy of medication lists completed by the triage nurse was 42.6%. 11 Most physicians rely on patients' drug lists when making a diagnosis and ordering tests and medications in the emergency department.…”
Section: Introductionmentioning
confidence: 99%